Identification of hub genes in congenital hypothyroidism and construction of the associated immune regulatory network - Shan, Mingliang; Xu, Li; Yang, Wenzhe; Liu, Shiguo (Frontiers in Immunology, 2025)
BackgroundThe absence of universal diagnosis and treatment recommendations for congenital hypothyroidism (CH) has led to suboptimal diagnostic and therapeutic outcomes. This study aimed to provide immunologically relevant evidence for the diagnosis and treatment of CH.MethodsDatasets related to CH were selected. Differentially expressed genes were screened, followed by enrichment analysis, weighted gene coexpression network analysis (WGCNA), protein–protein interaction analysis, and machine learning for the identification of hub genes. The reliability of these hub genes was verified through least absolute shrinkage and selection operator (LASSO) regression, box plot comparison, and receiver operating characteristic (ROC) curve analysis. Through gene set enrichment analysis (GSEA) of coexpressed genes, the common pathways of the hub genes and the inflammatory factors involved were identified. Immunoinfiltration analysis was carried out to verify the immunological correlation. Inflammatory factors and immune cells were screened by batch Mendelian randomization. Finally, the reliability of the hub genes, their relationships with inflammatory factors, and their impacts on cell function and the synthesis of free thyroxine (FT4) were validated through real-time quantitative polymerase chain reaction (RT–qPCR), enzyme-linked immunosorbent assay (ELISA), and cell proliferation experiments.ResultsMultiomics analysis confirmed that APP, DDB1, MRPS5, and MRPL33 were hub genes with low expression levels in CH. These genes negatively regulated IL-2, and subsequently, through the STAT5 and MTORC1 pathways, they positively regulated (CD27 on IgD- CD38+ B cells) and (CD27 on switched memory B cells)/CD244 and negatively regulated (CD33dim HLA DR+ CD11b- Absolute Count)/IL-18 and (CD28+ CD4-CD8- T-cell %T cell)/OPG, promoting the progression of CH. Increasing the expression levels of these hub genes could increase the activity of thyroid cells and promote the synthesis of FT4 through the abovementioned pathways.ConclusionsAPP, DDB1, MRPS5, and MRPL33 regulate the expression of IL-2, act on relevant immune cell subtypes through the STAT5 and MTORC1 pathways, negatively regulate IL-18 and OPG, and positively regulate CD244, thereby influencing the activity of thyroid cells and the synthesis of FT4.